4-(4-Chlorophenyl)-2,6-bis(1H-indol-3-yl)-1,4-dihydropyridine-3,5-dicarbonitrile ethanol monosolvate - Zhu, Song-Lei (International Union of Crystallography, 2012)
In the title compound, C(29)H(18)ClN(5)·C(2)H(6)O, the dihydropyridine ring adopts a strongly flattened envelope conformation, with a maximum deviation of 0.139 (2) Å from its best plane for the Csp (3) atom. The dihedral angles between the dihydropyridine ring plane and the two indole rings in positions 2 and 6 are 34.28 (5) and 40.50 (6)°, respectively. In turn, the benzene ring and the dihydropyridine ring are oriented at a dihedral angle of 74.69 (6)°. An intramolecular C—H⋯Cl hydrogen bond occurs. In the crystal, molecules are linked by N—H⋯N, N—H⋯O and O—H⋯N hydrogen bonds into layers parallel to (001). There are short C—H⋯Cl contacts between molecules in neighboring layers.